Research Progress of Traditional Chinese Medicine in Treatment of Myocardial fibrosis - Ren, Chunzhen; Liu, Kai; Zhao, Xinke; Guo, Huan; Luo, Yali; Chang, Juan; Gao, Xiang; Lv, Xinfang; Zhi, Xiaodong; Wu, Xue; Jiang, Hugang; Chen, Qilin; et al. (Frontiers in Pharmacology, 2022)
Effective drugs for the treatment of myocardial fibrosis are lacking. Traditional Chinese medicine (TCM) has garnered increasing attention in recentyears for the prevention and treatment of myocardial fibrosis. This article describes the pathogenesis of myocardial fibrosis from the modern medicine, alongwith the research progress. Reports suggest that Chinese medicine may play a role in ameliorating myocardial fibrosis through different regulatory mechanismssuch as reduction of inflammatory reaction and oxidative stress, inhibition of cardiac fibroblast activation, reduction in extracellular matrix, renin–angiotensin–aldosterone system regulation, transforming growth Factorβ-1(TGF-β1) expression downregulation, TGF-β1/Smad signalling pathway regulation, and microRNAexpression regulation. Therefore, traditional Chinese medicine serves as a valuable source of candidate drugs for exploration of the mechanism of occurrence and development, along with clinical preventionand treatment of myocardialfibrosis.